The Bostrichidae (Coleoptera) of Taiwan: a key to species, new records, and a lectotype designation for Sinoxylon mangiferae Chujo - Liu, L. Y.; Beaver, R. A.; Yang, J. T. (Zootaxa, 2006)
A key to the species of Bostrichidae from Taiwan is provided. Twelve species are recorded from Taiwan for the first time. Twenty-one species are believed to be established in Taiwan. A further seven species are recorded, but are not definitely known to be established. A lectotype is designated for Sinoxylon mangiferae Chujo.